1998
DOI: 10.1007/bf03043875
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management for villous tumors of the rectum

Abstract: We describe 10 patients with villous tumors of the rectum. Seven tumors showed severe dysplasia but only one invasion of the muscularis propria of the bowel wall. AII patients underwent a sphincter-conserving operation. There was one local recurrence which was treated by further local excision. One patient died of other causes, but the remainders recovered. Villous tumors of the rectum, even those showing severe dysplasia, can be adequately treated by local excision because they are adenomas. However, anterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…About 5% of such patients develop shock due to excessive potassium loss [6]. Katano et al reported on ten patients with villous tumors of the rectum who were treated in their hospital over the past 10 years, however, they did not report any cases with fluid and electrolyte depletion [5].…”
Section: Discussionmentioning
confidence: 99%
“…About 5% of such patients develop shock due to excessive potassium loss [6]. Katano et al reported on ten patients with villous tumors of the rectum who were treated in their hospital over the past 10 years, however, they did not report any cases with fluid and electrolyte depletion [5].…”
Section: Discussionmentioning
confidence: 99%